2003
DOI: 10.1002/chin.200310212
|View full text |Cite
|
Sign up to set email alerts
|

Hexacyclinol, a New Antiproliferative Metabolite of Panus rudis HKI 0254.

Abstract: Antibiotics Antibiotics U 1200Hexacyclinol, a New Antiproliferative Metabolite of Panus rudis HKI 0254. -Hexacyclinol (I), an unusual, oligocyclic metabolite is discovered in cultures of the title fungal strain. The oligocyclic structure contains epoxide and endoperoxide groups, double bonds, rings, and a spherical shape. The biosynthesis of (I) occurs via the terpenoid pathway. Hexacyclinol reveals moderate antibiotic activity and strong activities as inhibitor of oxidant generation in zymosan-stimulated poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Hexacyclinol is a widely known example of a natural product in which a constitutional structural reassignment stemmed directly from a computational evaluation of its 13 C NMR data. Structure 2a was initially assigned to this antiproliferative metabolite 36 . A total synthesis of this structure was reported 37 .…”
Section: Box 1 | Two Case Studies: Hexacyclinol (Constitution) and Vamentioning
confidence: 99%
“…Hexacyclinol is a widely known example of a natural product in which a constitutional structural reassignment stemmed directly from a computational evaluation of its 13 C NMR data. Structure 2a was initially assigned to this antiproliferative metabolite 36 . A total synthesis of this structure was reported 37 .…”
Section: Box 1 | Two Case Studies: Hexacyclinol (Constitution) and Vamentioning
confidence: 99%
“…A recent example is the high-profile case of the hexacyclinol structure (C 23 H 28 O 7 ). Schlegel et al [45] separated a natural product and suggested its structure based on the 2D NMR data. Le Clair [46] reported a synthesis of the structure, but Rychnovsky [47] suggested another structure based on 13 C chemical shift prediction using a GIAO-based quantum-mechanical DFT (Density Functional Theory) prediction method.…”
Section: Resultsmentioning
confidence: 99%
“…50 La Clair 51 claimed to have synthesized a substance with this structure in 2006. Based on spectroscopic studies, Grafe proposed 17 as its structure.…”
Section: Hexacyclinolmentioning
confidence: 99%